Identification of key residues in transmembrane 4 responsible for the secondary, low-affinity conformation of the human 1-adrenoceptor - Baker, Jillian G.; Proudman, Richard G.W.; Hill, Stephen J. (American Society for Pharmacology and Experimental Therapeutics, 2014)
The β1-adrenoceptor exists in two agonist conformations/states: 1) a high-affinity state where responses to catecholamines and other agonists (e.g., cimaterol) are potently inhibited by β1-adrenoceptor antagonists, and 2) a low-affinity secondary conformation where agonist responses, particularly CGP12177 [(−)-4-(3-tert-butylamino-2-hydroxypropoxy)-benzimidazol-2-one] are relatively resistant to inhibition by β1-adrenoceptor antagonists. Although both states have been demonstrated in many species (including human), the precise nature of the secondary state is unknown and does not occur in the closely related β2-adrenoceptor. Here, using site-directed mutagenesis and functional measurements of production of a cyclic AMP response element upstream of a secreted placental alkaline phosphatase reporter gene and accumulation of 3H-cAMP, we examined the pharmacological consequences of swapping transmembrane (TM) regions of the human β1- and β2-adrenoceptors, followed by single point mutations, to determine the key residues involved in the β1-adrenoceptor secondary conformation. We found that TM4 (particularly amino acids L195 and W199) had a major role in the generation of the secondary β1-adrenoceptor conformation. Thus, unlike at the human β1-wild-type adrenoceptor, at β1-TM4 mutant receptors, cimaterol and CGP12177 responses were both potently inhibited by antagonists. CGP12177 acted as a simple partial agonist with similar KB and EC50 values in the β1-TM4 but not β1-wild-type receptors. Furthermore pindolol switched from a biphasic concentration response at human β1-wild-type adrenoceptors to a monophasic concentration response in the β1-TM4 mutant receptors. Mutation of these amino acids to those found in the β2-adrenoceptor (L195Q and W199Y), or mutation of a single residue (W199D) in the human β1-adrenoceptor thus abolished this secondary conformation and created a β1-adrenoceptor with only one high-affinity agonist conformation.